Orderliness/Disorderliness Is Mentally Associated With Construal Level and Psychological Distance - Li, Kaiyun; Lv, Yingqi; Dong, Yingchao; Wang, Tianze; Wu, Jiayi; Zhang, Zhenxing; Li, Xinrui; Han, Ruikang; Lin, Fengxun (Frontiers in Psychology, 2019)
People are capable to explore and detect orderliness innately and to try to make the world in which they live more orderly rather than more disorderly. Construal level theory asserts that the same stimuli could be represented abstractly or concretely and psychological distance could affect the construal level. No research, however, has examined whether perceived orderliness/disorderliness would mentally associated with construal level and psychological distance. In this study, by using Implicit Association Test (IAT), we conducted 10 studies to examine this possibility. The results of studies 1A-1B showed that people tended to associate high-level construal concepts with orderliness concepts and low-level construal concepts with disorderliness concepts. In contrast, results of studies 2A-5B revealed that people associated psychologically proximal concepts with orderliness concepts and psychologically distal concepts with disorderliness concepts. These studies demonstrated that orderliness/disorderliness is associated with both construal level and psychological distance, yet, in opposite directions, suggesting that construal level and psychological may have distinct nature.